Development of a Redox‐Responsive Polymeric Profluorescent Probe. Issue 20 (31st August 2016) - Hansen, Kai‐Anders; Fairfull‐Smith, Kathryn E.; Bottle, Steven E.; Blinco, James P.
Abstract : Profluorescent nitroxides (PFNs) have emerged as an important class of imaging agents for monitoring intracellular redox status and levels of oxidative stress. However, the fast reduction of nitroxides upon incubation within cells limits the window of opportunity for detection. By increasing the concentration of nitroxides per fluorophore, their reduction to the corresponding hydroxylamines and the subsequent switch‐on of fluorescence can be delayed. Herein the preparation of nitroxide‐containing polymers of different chain length coupled to a fluorophore is reported and their reduction with pentafluorophenylhydrazine is examined. The fluorescence switch‐on kinetics and radical concentrations are monitored by fluorescence and electron paramagnetic resonance spectroscopy and compared to a conventional PFN bearing a single nitroxide moiety. The polymeric PFNs display significant delays in reduction and fluorescence switch‐on and higher turn‐on ratios than their single‐nitroxide counterparts. The results of this study indicate that polymeric PFNs are a promising architecture for future imaging agents. Abstract : Profluorescent nitroxides (PFNs) are an important class of imaging agents for monitoring intracellular redox status and oxidative stress levels. The preparation of nitroxide‐containing polymers of different chain length coupled to a fluorophore and their reduction with pentafluorophenylhydrazine are reported. The fluorescence switch‐on kinetics and radical concentrations are monitored by fluorescence and EPR spectroscopy and compared to a conventional single‐nitroxide PFN.